Upaya Pencegahan Diare Anak Melalui Edukasi Menggunakan Hand-Wash - Mita Ardila; Dwi Tiva Widyanti S. Humolungo; Danang Prasetyaning Amukti; Moch Saiful Bachri (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2024)
A disease that often occurs in developing countries, including Indonesia, is diarrhea. Diarrhea is the discharge of liquid or watery feces that occurs at least 3 times. In Indonesia, diarrhea is an Extraordinary Event (KLB) which is often accompanied by death. The general aim is to carry out training activities regarding diarrhea prevention education through hand washing to create knowledge about hygiene and sanitation for children at Muhammadiyah Sukonandin Elementary School to prevent diarrhea. The Participatory Action Research (PAR) method is used to emphasize participation and collaboration from various parties in managing action research research. In this method, 3 activities are implemented, namely socialization, discussion and mentoring. As a result of implementing PRODAMAT activities, Muhammadiyah Sukonandin Elementary School students obtained an average pre-test score of 60% and an average post-test score of 90%. Thus, it can be concluded that education can increase students' knowledge and understanding about preventing diarrhea through hand-washing.